1985
DOI: 10.3109/00016488509104788
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting the Occurrence of Acute Otitis Media among 2-3-Year-Old Urban Children

Abstract: The factors affecting the occurrence and recurrence of acute otitis media (AOM) were studied among 471 2-3-year-old children in two cities in Finland. Of these children, 188 had experienced greater than or equal to 3 attacks of AOM, 76 had had 1-2 attacks and 207 no otitis attacks (= control group). The study showed that the risk of recurrent AOM was increased among those children attending day-care nurseries as well as among those who had several siblings. Proneness to rhinorrhea and exposure to passive smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
7

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 26 publications
2
64
1
7
Order By: Relevance
“…Evidence from the literature suggests breastfeeding has continued signif icant protective effects to at least two years for gastrointestinal illness; 26 2-6 years for respiratory illness; 13,27 3-10 years for atopic eczema; 12,28 and three years for acute and recur rent otitis media. [29][30][31][32] • Diagnostic Classification: Data for age groups 0-12 months and 1-4 years were classif ied by principal diagnosis at the three or four-digit level according to the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM). This morbidity data was then mapped to AR-DRG 4.0 b y identifying separations where the principle diagnosis at the ICD-9-CM three-digit level best cor responded to the morbidity outcomes measured in the epidemiological studies (i.e.…”
Section: Morbidity/outcomesmentioning
confidence: 99%
“…Evidence from the literature suggests breastfeeding has continued signif icant protective effects to at least two years for gastrointestinal illness; 26 2-6 years for respiratory illness; 13,27 3-10 years for atopic eczema; 12,28 and three years for acute and recur rent otitis media. [29][30][31][32] • Diagnostic Classification: Data for age groups 0-12 months and 1-4 years were classif ied by principal diagnosis at the three or four-digit level according to the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM). This morbidity data was then mapped to AR-DRG 4.0 b y identifying separations where the principle diagnosis at the ICD-9-CM three-digit level best cor responded to the morbidity outcomes measured in the epidemiological studies (i.e.…”
Section: Morbidity/outcomesmentioning
confidence: 99%
“…8,9 When one counterbalances the weight of evidence for and against the association of allergic rhinitis and otitis media, publications with a less adequate investigative model tend to be on the side of accepting nasal allergy as a RF, which makes allergic rhinitis a RF that needs further study before more definitive conclusions can be drawn (level of evidence III).…”
Section: Resultsmentioning
confidence: 99%
“…67 Pukander et al also showed that children with siblings were more prone to recurrent episodes of AOM. 8 Having more than one sibling was significantly related to the early onset of otitis media. 68 However, the findings are not unanimous.…”
Section: Family Size (Siblings)mentioning
confidence: 97%
See 1 more Smart Citation
“…En población infantil, la exposición involuntaria al humo de cigarrillo aumenta la frecuencia de infecciones respiratorias bajas y de síntomas respiratorios, reduce el nivel esperado de VEF 1 y FEF 25-75 15 y aumenta el riesgo de desarrollar otitis media 16 . La exposición al humo de leña puede aumentar la frecuencia de infecciones respiratorias bajas 17 .…”
unclassified